Analysis of Laboratory Management Effectiveness in Biology Learning for Class X1 at SMA Negeri 2 Plus Panyabungan - Rahmadani Purba (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2023)
The laboratory is a special facility used for scientific activities. As a supporting tool in biology learning, every high school must have a laboratory with optimal management. This research aims to assess the effectiveness of the implementation of biology laboratory management at SMA Negeri 2 Plus Panyabungan, including aspects of planning, organizing, administering, arranging, and securing. The data used in this research were obtained through observation, questionnaires, interviews, as well as documentation, and subsequently analyzed descriptively.The results of the analysis show that SMA Negeri 2 Plus Panyabungan has implemented laboratory management well. The observation scores indicate that the category of laboratory management implementation at SMA Negeri 2 Plus Panyabungan is at a very good level, with a percentage reaching 91.75%. Likewise, the questionnaire and interview scoring results show a good category of laboratory management implementation, with a satisfactory percentage of 86.75%.Based on these findings, it can be concluded that the implementation of laboratory management at SMA Negeri 2 Plus Panyabungan is running well and effectively, providing a positive contribution to supporting the biology learning process.